Is Patent Foramen Ovale Closure More Effective Than Medical Therapy in Preventing Stroke Recurrence in Patients With Cryptogenic Stroke?: A Critically Appraised Topic. Issue 5 (September 2018) - Valencia-Sanchez, Cristina; Fortuin, F. David; Sweeney, John P.; Ingall, Timothy J.; Marks, Lisa A.; Wingerchuk, Dean M.; O'Carroll, Cumara B.
Abstract : Background: The clinical benefit of patent foramen ovale (PFO) closure in patients with cryptogenic stroke (CS) for recurrent stroke prevention has been a subject of extensive debate. Prior clinical trials failed to show superiority of PFO closure versus medical therapy. Meta-analyses suggested a possible benefit of PFO closure in select patients. Objective: The objective of this study was to critically assess current evidence regarding the efficacy of PFO closure compared with medical therapy for recurrent stroke prevention in patients with CS. Methods: The objective was addressed through the development of a structured critically appraised topic. This included a clinical scenario with a clinical question, literature search strategy, critical appraisal, results, evidence summary, commentary, and bottom line conclusions. Participants included consultant and resident neurologists, medical librarian, and vascular neurology and interventional cardiology content experts. Results: A randomized, controlled trial was selected for critical appraisal. This trial compared the efficacy of PFO closure and medical therapy in recurrent stroke prevention. A total of 663 patients who had a recent CS attributed to PFO, with a large interatrial shunt or with an associated atrial septal aneurysm were included. No stroke occurred among the 238 patients in the PFO closure group, whereas 14 of the 235 patients in the antiplatelet therapy group had recurrent strokes. Conclusions: Among patients who had a recent CS attributed to PFO with a large interatrial shunt or with an associated atrial septal aneurysm, the rate of stroke recurrence was lower among those assigned to PFO closure combined with antiplatelet therapy than among those assigned to antiplatelet therapy alone.